Cone beamed computed tomography in pediatric dentistry: Concepts revisited - Mehta, Vivek (J Oral Biol Craniofac Res, 2020)
Oral diagnosis and treatment planning is of utmost importance in pediatric dentistry. Although intraoral and conventional radiographic procedures have been used extensively since decades, there two-dimensional representation has raised many questions. Cone beamed computed tomography with 3-D technology is a replacement for conventional 2-D imaging and has a wide application among child patients in pediatric dentistry. This article therefore deals with current facts and myths about clinical situations where CBCT is indicated in pediatric patients.